INFLUENCE OF EDUCATIONAL INNOVATION ON THE CREATIVE DEVELOPMENT OF FUTURE TEACHERS - Мартинюк, В.В.; Мартинюк, Л.І. (Modern engineering and innovative technologies, 2024)
The article substantiates the essence of educational innovation as a separate field of scientific knowledge. Modern requirements for professional training of future teachers in the development of creative abilities are presented. The expediency of using i